Predictive Ability of Humor Styles of Psychological Well-being among Universities Students - Ahmad Shraifin; Abeer Alrefai; Amal Nemrat (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to reveal the predictive ability of humor styles of psychological well-being among universities students. The study sample consisted of 750 students (225 males and 525 females). They were chosen by a convenient sampling technique. Students were enrolled in second and summer semesters for the academic year (2018\2019), To achieve the aims of the study; a humor styles scale was developed by Martin and his colleagues (2003), and a psychological well-being scale developed by Ryff and Keyes (1995) were used. The results revealed astafistically significant differences in humor styles attributed to sex in favor of females in the style of affiliative humor, and in humor self- enhancing in favor of males with aggressive humor and self-defeating humor styles. Moreover, the results showed that the level of psychological well-being for universitiy students was average on the total scale. More results and consequences are discussed in the paper.